THE STUDY OF THE PROCESSES OF STRUCTURE FORMATION OF FILLED SOLUTIONS BASED ON ALKYL RESORCINOLS - Mamonova, T. V. (Science and Transport Progress, 2004)
The article presents the results of experimental and theoretical study of structure-forming peculiarities in alkylresorcin-based filled-in composites. A high efficiency of the mortars for construction of anti-filtration screens in facilities, operated in conditions of exposure to ground waters, has been demonstrated.